Scour around a side-weir at a 30° section of a 180° alluvial curved channel - Agaccioglu, Hayrullah; Onen, Fevzi; Toprak, Z. Fuat (WILEY, 2007)
Local depths of clear-water scour around side-weirs located at a 30 degrees section of a 180 degrees alluvial bend have been investigated experimentally in this paper. Relations between the depth of clear-water scour as a function of time and approach flow intensity have been established. Regression analysis has been applied between the equilibrium depth of scour and the dimensionless parameters of approach flow intensity (V-1/V-c, approach flow velocity/critical velocity at the threshold conditions of bed material), water head ratio ((h(1)-p)/h(1), weir head over the side-weir/water depth in the main channel), and weir crest height (b/p, width of main channel/side-weir crest height) at 0 = 30 degrees. Although there is no scour when approach flow intensity is less than 0.55, the scour equilibrium depth increases almost linearly with the ratio of approach flow intensity, and the maximum value of scour depth occurs at a depth when the approach flow intensity is equal to 1.0 at the 30 degrees section of a 180 degrees alluvial curved channel. The location of the maximum scour hole occurs at the downstream of side-weir sections close to the outer bank of the main channel and it moves toward the downstream direction with an increase of the dimensionless parameters of approach flow intensity as well as the water head ratio, the weir crest height and the side-weir length (L/r, length of side-weir/radius of main channel from the bend centre). Copyright (c) 2007 John Wiley & Sons, Ltd.
Keywords: side-weir; separation zone; reverse flow; scour depth; alluvial bend; DISCHARGE COEFFICIENT; FLOW; Agriculture; Water Resources